Contemporary Practices of Customary Conflict Resolution Mechanism: The Roles of Bokkuu (cultural) Centers among Oromo, Ethiopia - Jemila Adem Hussein; Terefe Mitiku; Megersa Regassa; Waktole Hailu (Humanus: Jurnal Ilmiah Ilmu-ilmu Humaniora, 2020)
Conflict is a natural and unavoidable part of human existence. It is resulting from individual or groups that differ in attitude, beliefs, values or needs. This study explored Contemporary Practices of Customary Conflict Resolution Mechanism in and around Ambo district. The study answered the following basic questions: What are the roles of Bokkuu centers in handling conflict/disputes? How did the Bokkuu centers resolve conflict/disputes? Who are the main actors that guide the conflict resolution procedure at the Bokkuu centers? What types of conflict is resolved at the three Bokkuu centers? Qualitative research methods were used to understand the complexity of Oromo cultural peacemaking and how this takes shape within the culture of the Oromo custom. Techniques of collecting data were interviewing knowledgeable elders, field observation, and Focused Group Discussion were employed. The study discovers that the participants of the study agree that cultural conflict resolution are more effective in fact finding and resolve the disagreement between the disputants than that of formal courts. Because of its effectiveness in conflict resolution and truth finding traditional conflict resolution mechanisms is extensively serving in the study area. The ways judicial procedures take place is more reliably and open for disputants and any interested body that have an idea about the issue.  The members of the council are the main actor of the cultural centers; they are five in number and belong to different clans.